2011
DOI: 10.48550/arxiv.1112.1682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entanglement Entropy of the Early Universe in Generalized Chaplygin Gas Model

Abstract: We provide an explicit calculation of the evolution of the cosmic entanglement entropy in the early universe before the matter dominant era. This is made possible by invoking the generalized Chaplygin gas (GCG) model, which has the advantage of preserving unitarity and providing a smooth transition between the inflation epoch and the radiation dominant era. The dynamics of the universe is described by the quantization in the minisuperspace of the GCG model, following the prescription proposed by Wheeler and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…5) as well as the tree-level inhomogeneous part (Fig. 6) previously observed in [17]. The persistence of the entropy minimum after putting back some of the degrees of freedom suggests that it is a real physical feature and we expect this entropy minimum not be completely erased by higher order corrections.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…5) as well as the tree-level inhomogeneous part (Fig. 6) previously observed in [17]. The persistence of the entropy minimum after putting back some of the degrees of freedom suggests that it is a real physical feature and we expect this entropy minimum not be completely erased by higher order corrections.…”
Section: Discussionsupporting
confidence: 56%
“…In particular, a decrease of tripartite entropy after inflation is shown in [16], which inspires us to consider the evolution of bipartite entropy from quantum entanglement. Indeed, in a recent effort by two of the present authors (PC & YN) [17], it was found that a minimum of the entanglement entropy induced from the entanglement between cosmological perturbations is reached at an early stage of the inflation. The calculation made there, however, was classical.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…In particular, a decrease of tripartite entropy after inflation is shown in [21], which inspires us to consider the evolution of bipartite entropy from quantum entanglement. Indeed, in a recent effort by two of the present authors (PC & YN) [22], it was found that a minimum of the entanglement entropy induced from the entanglement between cosmological perturbations is reached at an early stage of the inflation. The calculation made there, however, was classical.…”
Section: Jcap02(2014)040mentioning
confidence: 51%